Wood – As a Decorative Material of the Interior - Rakhmatova Mekhriniso Murodovna; Kaxorova Gulshan Sergeevna (Researchparks Publishing, 2022)
This article highlights the many possibilities and advantages of wood as an interior decoration and decorative material, its convenience, environmental friendliness and durability, decors, its use in the decoration of modern interiors, taking into account all its features. To what extent is the wood used in recent years, what type of wood should be used in the interior, what wood furniture is used in the interior? Similar questions can be answered in this article. Wood is an ideal raw material in terms of safety and naturalness, used in construction and repair for many centuries. Therefore, wood is widely used in interior design of houses, apartments and courtyards, roofing, construction of columns, beams, furniture for buildings and houses. Despite the abundance of practical artificial materials today, man continues to strive for nature and ecological purity in the decoration of buildings. Many designers are choosing wood to decorate the interior. This is due to the fact that wood has many advantages. Wooden furniture is often used to create a modern interior. It is distinguished not only by its esthetic appearance, but also by its long service to the people. The introductory part of the research, the types and process of research, its results and final conclusions are presented.